2021
DOI: 10.1038/s41419-021-03888-1
|View full text |Cite
|
Sign up to set email alerts
|

PRDX2 promotes the proliferation of colorectal cancer cells by increasing the ubiquitinated degradation of p53

Abstract: Colorectal cancer is the most common gastrointestinal cancer and causes severe damage to human health. PRDX2 is a member of the peroxiredoxin family reported to have a high level of expression in colorectal cancer. However, the mechanisms by which PRDX2 promotes the proliferation of colorectal cancer are still unclear. Here, the results indicated that PRDX2 expression was upregulated in colorectal cancer and closely correlated with poor prognosis. Functionally, PRDX2 promoted the proliferation of colorectal ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…2D), was described to interact with MDM2 to promote its proteasomal degradation (as shown in Fig S1D under starvation) and p53 stabilization [39]. Additionally, Peroxiredoxin-2 (PRDX2), recently reported as promoting p53 ubiquitination and degradation [40], was found de-enriched upon starvation (Fig. 2D).…”
Section: Proximity-based Labeling Proteomics Reveals P53 Interactome Under Starvationmentioning
confidence: 74%
“…2D), was described to interact with MDM2 to promote its proteasomal degradation (as shown in Fig S1D under starvation) and p53 stabilization [39]. Additionally, Peroxiredoxin-2 (PRDX2), recently reported as promoting p53 ubiquitination and degradation [40], was found de-enriched upon starvation (Fig. 2D).…”
Section: Proximity-based Labeling Proteomics Reveals P53 Interactome Under Starvationmentioning
confidence: 74%
“…PRDX2 was associated with prognosis in multiple cancers, such as colorectal cancer ( 11 ), hepatocellular carcinoma ( 23 ) and esophageal squamous cell carcinoma ( 24 ). Though PRDX2 did not predict HNSCC prognosis, we still found that PRDX2 was positively associated with aggressive phenotype, such as angiogenesis, EMT, invasion, metastasis and proliferation, which was in line with oral squamous cell carcinoma (OSCC).…”
Section: Discussionmentioning
confidence: 99%
“…PRDX1 is up-regulated in some tumors such as pancreatic ductal adenocarcinoma, nonsmall cell lung cancer, cervical cancer and breast cancer, and promotes the growth and metastasis of cancer cells (6)(7)(8)(9). PRDX2 facilitates the proliferation of colorectal cancer cells and non-small cell lung cancer cells (10,11). PRDX3 and PRDX5, two mitochondrial PRDXs, are associated with unfavorable survival in endometrial cancer and ovarian cancer (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is reported that Gpx1 is related to diabetes, and Gpx1 overexpressed mice exhibited insulin resistance, hyperinsulinemia, obesity and hyperglycemia [43,44]. Prdx2 has a high expression level in various cancers, such as lung, colorectal, and gastric cancers [22]. Moreover, Prdx2 has been reported to be involved in arthrosclerosis progression [23].…”
Section: Discussionmentioning
confidence: 99%
“…This implies the specific and non-redundant functions of erythrocyte Prdx2 in peroxide removal and the protection of erythrocytes against oxidative damage [14]. Prdx2 has been reported to have a high expression level in various cancers, including in lung, colorectal, and gastric cancers [22]. Moreover, Prdx2 has been reported to be involved in the progression of arthrosclerosis [23].…”
Section: Introductionmentioning
confidence: 99%